2022
DOI: 10.3390/molecules27103143
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Botulinum Toxin in Dermatology—Current State of the Art

Abstract: Botulinum toxin (BoNT) is a neurotoxin produced by the Clostridium botulinum bacteria. Among seven different isoforms, only BoNT-A and BoNT-B are commercially used. Currently, botulinum toxin has been indicated by the U.S. Food and Drug Administration in several disorders, among others: chronic migraine, hyperhidrosis, urinary incontinence from detrusor overactivity, or cosmetics. However, there are numerous promising reports based on off-label BTX usage, indicating its potential effectiveness in other disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 115 publications
0
9
0
4
Order By: Relevance
“…Występuje siedem różnych rodzajów egzotoksyn: A, B, C, D, E, F, G, z czego komercyjnie używa się BoNT-A i BoNT-B. (3,6) Pierwszy raz została użyta w 1980r. przez Edwarda Schantza i Alana B. Scotta w terapii leczenia zeza.…”
Section: Toksyna Botulinowaunclassified
See 2 more Smart Citations
“…Występuje siedem różnych rodzajów egzotoksyn: A, B, C, D, E, F, G, z czego komercyjnie używa się BoNT-A i BoNT-B. (3,6) Pierwszy raz została użyta w 1980r. przez Edwarda Schantza i Alana B. Scotta w terapii leczenia zeza.…”
Section: Toksyna Botulinowaunclassified
“…przez Edwarda Schantza i Alana B. Scotta w terapii leczenia zeza. (3,7) Obecnie toksyna botulinowa jest szeroko stosowana w różnych dziedzinach medycyny, m.in. w medycynie estetycznej, neurologii, okulistyce, dermatologii, ginekologii, ortopedii, otolaryngologii, chirurgii, stomatologii.…”
Section: Toksyna Botulinowaunclassified
See 1 more Smart Citation
“…Serotypes A and B are currently in clinical usage, but botulinum neurotoxin A (BoNT-A) is the most commonly used [15,16]. Concerning temporary muscle paralysis capability, wide clinical treatment has been adopted [16][17][18]. Apart from inhibiting acetylcholine release from a presynaptic neuromuscular junction, studies found that BoNT-A can reduce skin inflammation by inhibiting mast cell degranulation and blocking cholinergic stimuli to apocrine and eccrine glands [19].…”
Section: Introductionmentioning
confidence: 99%
“…There are several conditions for which BoNT is not yet approved for clinical use, but off-label use has been presented, with beneficial effects, for example, in dermatology [ 33 , 34 , 35 ], primary headaches other than migraine [ 36 ], depression [ 37 ], and neuropathic pain [ 38 , 39 ]. One large area in which the off-label use of BoNT has been practiced for the last two decades is dermatology, for various conditions that appear with or without itch [ 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%